The Efficiency of Apple Vinegar as A Solvent in Comparison to Water and Ethanol for The Extraction of Some Plants used Against Candida Spp. Biofilm Formation - Mohammed, Sinai W.; Jabbar, Faheema; Nayyef, Hanan J.; Al-Malkey, Maysaa K.; Misha’al, Khawla I.; taqi, Estabraq Ab. (Iraqi Journal of Science, 2021)
Apple vinegar has many uses that include burn and wound healing and as an antimicrobial agent against different microorganisms, but not as a solvent. Therefore, this study aimed to use commercial apple vinegar as solvent to the plants of roselle (Hibiscus sabdariffa), green tea (Camellia sinensis), and clove (Syzygium aromaticum). The effects of apple-vinegar extracts of these plants were compared with those of aqueous and ethanolic extracts against biofilm formation by Candida genus. Clove vinegar extract demonstrated antibiofilm activity against C. albicans, alone (2.4907± 0.382) or in combination with the antifungal agents fluconazole (1.689±0.33), nystatine (1.941±0.64), and clotrimazole (2.0353±0.71819). These plant extracts possessed a variable number of antimicrobial compounds, as tested by the HLPC technique. Therefore, apple vinegar was the most efficient solvent, in comparison with the other solvents used in this study, to obtain some phytochemical compounds from the tested plants that have antibiofilm activity against C. albicans.